2004
DOI: 10.1111/j.1432-1033.2004.04134.x
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of the interaction of Limulus polyphemus endotoxin neutralizing protein with lipopolysaccharide

Abstract: Endotoxin-neutralizing protein (ENP) of the horseshoe crab is one of the most potent neutralizers of endotoxins [bacterial lipopolysaccharide (LPS)]. Here, we report on the interaction of LPS with recombinant ENP using a variety of physical and biological techniques. In biological assays (Limulus amebocyte lysate and tumour necrosis factor-a induction in human mononuclear cells), ENP causes a strong reduction of the immunostimulatory ability of LPS in a dose-dependent manner. Concomitantly, the accessible neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 46 publications
3
26
0
1
Order By: Relevance
“…These values are consistent with those of other active antimicrobial peptides obtained using fluorescence spectroscopy [25]. ITC experiments, carried out at 37°C, revealed that binding of the peptide to LPS is an exothermic process, driven by the electrostatic interactions between the positively charged peptide and the negatively charged LPS as observed for other antimicrobial peptides reported in the literature [51,53,54].…”
Section: Discussionsupporting
confidence: 90%
“…These values are consistent with those of other active antimicrobial peptides obtained using fluorescence spectroscopy [25]. ITC experiments, carried out at 37°C, revealed that binding of the peptide to LPS is an exothermic process, driven by the electrostatic interactions between the positively charged peptide and the negatively charged LPS as observed for other antimicrobial peptides reported in the literature [51,53,54].…”
Section: Discussionsupporting
confidence: 90%
“…We think it is noteworthy that many of these proteins, in particular LALF, bactericidal permeability increasing protein (BPI) (41), and LPS-binding protein (LBP) (42), possess functions that extend beyond the mere binding of LPS. It has been hypothesized that the eukaryotic structural homolog LALF participates in not only the binding of LPS but also in its transport to and insertion into phospholipids membranes as part of the Limulus host immune response (23,35). LBP and BPI are elongated in shape and contain a duplicated fold similar to that of LptE.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LptE binds to and solubilizes LPS adhered to a CM3 chip. Because the structure of LptE shows homology to the eukaryotic protein LALF, which binds and transports LPS (23,35), we wondered whether LALF would show similar binding interactions with LPS in our SPR assay. In fact, LALF is also able to extract LPS from the chip surface (Fig.…”
Section: Positively Charged Residues At the Extracellular Side Of Lptmentioning
confidence: 99%
“…Several studies have investigated the LPS binding ability of the recombinant ALF [23]. Besides, it was proposed that the bactericidal effect of ALF like ALFPm3 from shrimp was due to its binding activity to components of the bacterial cell-wall [24].…”
Section: Membrane Integrity Assaymentioning
confidence: 99%